Inventory of herbs plants at three different locations in forest education of Mulawarman University, Samarinda, East Kalimantan, Indonesia - Sutedjo; Rita Diana; Yasfini Hurum Mercury (Journal of Agriculture and Applied Biology, 2021)
Many plants have the potential to be medicinal from the herbaceous group. Herbaceous plants have short, small steam and have a wet trunk because they contain many water and non-woody. This research aims to inventory species of herbaceous plants that can be medicinal plants and other uses in three different locations. The results showed that 12 species were found in the slope area, 340 individuals. The highest number of SDRn of 29.26% was Nephrolepis biserrata (SW.) Schott. In the ramp, the area has been found of 11 species of herbaceous, 215 individuals. The highest number of SDRn of 34.81% was Phrynium pubinerve Blume. In a hill, area has been found 16 species of herbaceous, 542 individuals. The highest number of SDRn of 38.72% was Phrynium pubinerve Blume. Dominance index (C) in three locations research was 0.26, 0.23 and 0.31. Similarity index (ISs) in three locations was 60.87% (slope-ramp: high), 59.26% (slope-hill: medium) and 57.14% (ramp-hill: medium). There were 11 species as medicinal plants, 17 species as ornamental plants, and 2 species as crafts.